AB0552 Antiphospholipid antibodies in giant cell arteritis. (15th June 2017) - Hocevar, A; Jese, R; Rotar, Z; Zigon, P; Cucnik, S; Tomsic, M
Abstract : Objectives: The aim of our prospective study was to evaluate the role of antiphospholipid antibodies (aPL) on the clinical presentation of giant cell arteritis (GCA). Methods: GCA patients diagnosed for the first time between 1. September 2011 and 31. December 2016 at our secondary/tertiary rheumatology center and in whom aPL-Abs were determined at presentation were included. We studied four types of aPL-Abs in patient's sera: lupus anticoagulants (LA), IgG and IgM isotype of anticardiolipin antibodies (aCL), of antibodies to β2-glycoprotein 1 (aβ2GP1) and of antibodies to phosphatidylserine-prothrombin complex (aPS/PT). LA activity was determined only in patients not receiving anticoagulant therapy. A dilute Russell viper venom time test was used and a ratio above 1.2 was considered positive. aCL, aβ2GPI and aPS/PT were measured using an in-house ELISA. A value above the 99th percentile of healthy control population was taken as positive. Results: During the 64-month observation period we performed all aPL-Abs tests in 121 GCA patients (81 females (66.9%); median (IQR) age 73.8 (66.4; 78.7) years). We found LA, aCL, aβ2GP1 and aPS/PT in 59 (48.8%), 55 (45.5%), 15 (12.4%) and 18 (14.9%) cases, respectively. Fifty-four patients (44.6%) were single, 25 (20.7%) double, 13 (10.7%) triple and 1 (0.8%) quadruple aPL-Abs positive. 28 patients (23.1%) were aPL-Abs negative. Clinical characteristics of individual aPL-Ab type groups are presented in Table 1 . There was one case of concurrent venous thrombotic event in our group (in a patient without aPL-Abs). The presence of aCL was associated with extracranial large vessel vasculitis (RR 1.8 (95% CI 1.1–2.9)). Double- or triple-positivity for any combination of "classic" aPL (LA and/or aCL and/or abeta2GP1) emerged as a marker of severe visual manifestations (RR of 2.1 (95% CI 1.1–4.3) for permanent or transient visual loss in case of double or triple aPL positivity vs. LA, aCL and aβ2GP1 negative cases). At least 1 year follow-up data (median (IQR) of 103 (54; 105) weeks) were available for 73 patients. 32 patients (43.8%) relapsed, most frequently those with positive aβ2GP1 (62.5%). Conclusions: Our results indicate that aCL could identify GCA patients with extracranial large vessel disease. The double- or triple-positivity for any combination of LA and/or aCL and/or aβ2GP1 seems to be a marker of severe visual manifestations. Disclosure of Interest: None declared